PENGEMBANGAN LEMBAR KERJA SISWA DENGAN PENDEKATAN SAINTIFIK BERBASIS KEMAMPUAN PEMECAHAN MASALAH - Nora Septina; Farida Farida; Komarudin Komarudin (Universitas Islam Negeri (UIN) Mataram, 2018)
The current study is a development research aiming to produce scientific-approach student worksheets which is based on mathematical problem solving ability. Borg and Gall development model modified by sugiyono is utilized in this study. Questionnaire is given to experts to find out the feasibility of the product and to learners and educators to know the attractiveness of the product. The results of the study indicates that the assessment of the experts is very feasible (83% of material experts, and 85% of media experts), the response of learners and educators is very interesting (88% small group trial, 89% field trials and 88% educator test) .